The Grooming of Children for Sexual Abuse in Religious Settings: Unique Characteristics and Select Case Studies - Raine, Susan (International journal of coercion, abuse and manipulation IJCS, 2022)
This article examines the sexual grooming of children and their caregivers in a wide variety of religious settings. We argue that unique aspects of religion facilitate institutional and interpersonal grooming in ways that often differ from forms of manipulation in secular settings. Drawing from Christianity (Catholicism, Protestantism, and Seventh Day Adventism) and various sects (the Children of God, the Branch Davidians, the Fundamentalist Latter-Day Saints, a Hindu ashram, and the Devadasis), we show how some religious institutions and leadership figures in them can slowly cultivate children and their caregivers into harmful and illegal sexual activity. A number of uniquely religious characteristics facilitate this cultivation: theodicies of legitimation; power, patriarchy, obedience, protection, and reverence toward authority figures; victims’ fears about spiritual punishments; and scriptural uses to justify adult-child sex.